2016
DOI: 10.11138/mltj/2016.6.4.433
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic treatment of the atraumatic shoulder instability: a case series with two-year follow-up evaluation

Abstract: SummaryBackground: The purpose of this work is to evaluate the results of arthroscopic capsulolabroplasty in patients affected by atraumatic shoulder instability (ASI). Methods: A retrospective review was performed of 10 patients (7 women and 3 men) who underwent arthroscopic treatment of symptomatic ASI. Mean age at evaluation was 27.9 (19-35) years and the mean follow-up was 23.3 (12-37) months. We evaluated recurrence rate, range of movement, apprehension and relocation tests, hyperlaxity, and sport activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Besides, it was also controversial that the loss of range of motion (ROM) after arthroscopic Bankart repair was minor to that after open capsular repair [17]. Some meta-analysis studies reported that Bankart repair can provide better recovery of ER at 90° abduction [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, it was also controversial that the loss of range of motion (ROM) after arthroscopic Bankart repair was minor to that after open capsular repair [17]. Some meta-analysis studies reported that Bankart repair can provide better recovery of ER at 90° abduction [18].…”
Section: Discussionmentioning
confidence: 99%
“…One interesting thing we found was that most Chinese patients, especially older patients, were more willing to use complimentary care modalities or Bankart repair due to rapid recovery. Actually, according to years of work experience, capsular shift can be a good alternative if facing anteroinferior or multidirectional type of shoulder, but not including severe bone defect [17, 26]. As for the limitation of the thesis, further study was still demanded in this field.…”
Section: Discussionmentioning
confidence: 99%